Self Injury yang Tercermin Pada Tokoh Ayumu dalam Manga Raifu Karya Keiko Suenobu - Susmitha Awandari, Komang (Humanis; Vol 22 No 2 (2018), 2018)
This research’s title is “Self Injury Reflected in Ayumu Character on the Manga Raifu by Keiko Suenobu’s”. This research aims to determine the characteristics of  self injury, factors cause and the impact of self injury reflected on Ayumu character. This research used theory of literary psychology by Wellek and Warren (1993),self injurious behaviours theory by Walsh (2006), and semiotics theory by Danesi (2011). The results of this research showed that there were three characteristics of self injury experienced by Ayumu character, namely hatred to herself, depression dued to trauma or severe stress triggered by a person’s loss, sexual abuse, oppression, and tendency to avoid others. The factors that cause Ayumu to became self injury characters were the lack of affection and attention in the family, the lack of effective communication, and the feeling of neglection.. Moreover, two negative impacts from self injury on Ayumu character, were found the addicted characters against self injury action and anti-social personality.